ON THE CONTROVERSIAL LOCALIZATION OF THE TSAKHAR FORTRESS IN THE PASCHAL FORTIFICATION - Trebeleva, Galina Viktorovna; Sakania, Suram Mihajlovic; Kizilov, Andrej Sergeevic; Glazov, Konstantin Anatol'evic (History, Archeology and Ethnography of the Caucasus, 2023)
The issue of localization of one or another toponym known from narrative sources is often ambiguous and causes discussions in the scientific community. This article is devoted to the analysis introduced into scientific circulation by Yu.N. Voronov and the well-established identification of a famous monument on the left bank of the Kodor – the Pskal fortification with the Tzakhar fortress, described by Agafius of Mirineisky. The Pskal fortification is a temple surrounded by a fortress wall with a total area of 1100 m². The authors of the article carried out a detailed analysis of the geographical location of the fortification, made a full-scale inspection, created photogrammetric models of the landscape and the temple itself. The geographical location of the monument showed that the Pskalsky fortification was connected with the region of the left bank of the Kodor River, and not with the Tsebelda Valley and the Misimians, which Agathius of Mirineisky describes, and which were located on the right bank of this river. The absence of a description of the crossing over the river and the inconsistency of the fortification area described in the source regarding the Ttsakhar fortress allows us to say that the identification of the Pskal fortress with Ttsakhar is premature and extremely controversial. An analysis of the design features of the temple made it possible to find a number of analogies among other monuments of the region, including those studied archaeologically, thanks to which we can state: monuments of this type: small temples with a semicircular apse inscribed in a common rectangular outline, with two semicircular niches on both sides of the apse semicircle could not have been built later than the 12th century, but they are not monuments of the Tsebelda era either. They can be attributed to the era of the emergence of a single Abkhazian kingdom. Thus, the fortification on Mount Pskal is not the ancient Misimian fortress Ttsakhar from the era of late antiquity, but a monument of the medieval history of the Abkhazian kingdom, which still requires its detailed study.
Keywords: Abkhazia; Misimians; Zebeldin valley; fortresses; Kodor river; temples; rectangular apse; niches; Abkhaz kingdom.